Nel silenzio della mia stanza… Riflessioni pedagogiche sul fenomeno Hikikomori - Certini, Rossella; Distefano, Christian (Studi sulla Formazione/Open Journal of Education, 2023)
The category of Care, understood as an ontological construct of pedagogy, is a topic of research and in-depth study by many researchers for several reasons: for the importance it has in the epistemic framework of pedagogical science and for the centrality that this category has in educational practice. Talking about Care means to speak of a fundamental topical category today. The PRIN project Pratiche educative di prevenzione e ben-essere per gli Hikikomori. Dalla onsapevolezza alla “Cura educativa”, presented in 2022 and awaiting evaluation, sought to combine the category of Care with the educational emergency of the Hikikomori: they are young people locked inside their own room, who manifest their vulnerability by cancelling all kinds of relationships except the virtual one.